Chert procurement in Corsica during the Neolithic: Inferring social territories in the Tyrrhenian islands - Céline Leandri; Paul Fernandes (Journal of Lithic Studies, 2020)
From the Neolithic, foreign siliceous materials were imported into Corsica as the island lacks local chert and obsidian. Such a context constitutes a real opportunity to investigate the relationship of the island with surrounding areas, in perspective with cultural evolutions. For 20 years, chert sourcing studies were carried out. We took into account 26 sites, dating from the Ancient Neolithic to the Final Neolithic. The work is based on non-destructive petro-archaeological observations of the artefacts. and on the survey and characterization of Sardinian sources (320 samples collected and 60 different lithotypes characterized).